Encapsulated Co3O4/(SiAl@Al2O3) thermal storage functional catalysts for catalytic combustion of lean methane. (25th November 2020) - Li, Danyang; Xu, Ruidong; Tian, Mengshuang; Jia, Yuanwei; Gu, Zhenhua; Zhu, Xing; Li, Kongzhai
Graphical abstract: In the present work, encapsulated Co3 O4 /(SiAl@Al2 O3 ) thermal storage functional catalysts which couple Co3 O4 catalysts and SiAl@Al2 O3 phase change materials are proposed and firstly applied for catalytic combustion of lean methane to achieve the high efficiency of lean methane utilization. It is found that thermal storage catalysts retain the high latent heat of SiAl@Al2 O3 phase change material. In addition, such thermal storage catalysts show significant efficiency of lean methane conversion than pure Co3 O4, and it can also keep the methane conversion at a high level for a long time even if the external heat source disappears. This indicates that the effective heat management of Co3 O4 /(SiAl@Al2 O3 ) thermal storage catalysts during methane combustion process plays a crucial role in determining the catalytic activity via improving the thermal runaway and hot spots problems in catalyst bed and reducing heat loss. Particularly, the Co3 O4 /(SiAl@Al2 O3 -30 wt%) catalyst behaves the excellent catalytic activity and heat storage performance. Highlights: Co3 O4 /(SiAl@Al2 O3 ) thermal storage catalysts couple SiAl@Al2 O3 PCMs and Co3 O4 . Effective heat management of PCMs-catalysts is a crucial role in determining activity. Thermal storage catalysts show high efficiency of methane conversion than Co3 O4 . Thermal storage catalysts keep methane conversion at high levels for a long time. Catalyst with 30 wt% PCM shows the best activity and heat storage performance. Abstract: It is well known that the structural problem between the autothermal operation and the outside utilization of heat in the catalytic combustion system and the runaway on catalyst bed is hard to avoid during the combustion process. Herein, the encapsulated Co3 O4 /(SiAl@Al2 O3 ) thermal storage functional catalysts which couple Co3 O4 catalysts and SiAl@Al2 O3 phase change materials are proposed and firstly applied for catalytic combustion of lean methane to improve the thermal environment of the catalyst bed and achieve the high efficiency of lean methane utilization. The thermal management behaviors of such thermal storage functional catalysts and the dynamic coupling effect between heat storage/release characteristics of catalysts and catalytic performance during methane combustion process are investigated in detail. It is found that the encapsulated Co3 O4 /(SiAl@Al2 O3 ) thermal storage catalysts retain the high latent heat of SiAl@Al2 O3 phase change material (410 J/g) and the values vary from 280 J/g to 30 J/g when the SiAl@Al2 O3 content decreases from 90 wt% to 10 wt%. When applying the catalysts to catalytic combustion of lean methane, such thermal storage functional catalysts with high thermal storage density show significant efficiency of lean methane conversion than pure Co3 O4, and it can also keep the methane conversion at a high level for a long time even if the external heat source disappears. This indicates that the effective heat management of Co3 O4 /(SiAl@Al2 O3 ) thermal storage catalysts during methane combustion process plays a crucial role in determining the catalytic activity via improving the thermal runaway and hot spots problems in catalyst bed and reducing heat loss. However, the content of SiAl@Al2 O3 needs to be carefully regulated to avoid the decrease of activity resulting from the low active Co3 O4 content. Particularly, the Co3 O4 /(SiAl@Al2 O3 -30 wt%) catalyst shows a competitive activity (e.g., T10, T50 and T90 at 226, 282 and 370 °C) and it surpasses the activity of pure Co3 O4 in literatures although the active Co3 O4 content is significantly lower than them. After turning off the heat source for 37 min, its methane conversion can still reach 50%, which is twice that of pure Co3 O4 . The present approach for thermal management in catalytic methane combustion reaction will provide good references for solving the problems (e.g., temperature runaway and hot-spot) in fixed bed reactors during other complex heterogeneous chemical reactions.